Optimizing Public Service Effectiveness through Digital-Based Archival Management at Bandung City Land Office - Poppy Citra Luthfiya; Muhammad Taufiq (Trescode Green Organization, 2024)
Archival management is an important part in supporting the effectiveness of public services, especially in government agencies engaged in land administration. This study aims to analyze archival management at the Bandung City Land Office in supporting the effectiveness of public services. This study uses a qualitative descriptive method with data collection techniques through observation, archival, and literature studies. Data were obtained from archive and correspondence management activities at the Bandung City Land Office and supported by national and international references related to digital archive management. The results of the study indicate that archival management has been carried out through a systematic process of administration, recording, distribution, validation, and archiving of archival s. The implementation of digital systems such as E-Surat, E-Office, KKP, and SITATA helps improve the efficiency of land administration. Effective archival management has a positive impact on increasing the speed of service, information accuracy, administrative transparency, and public service accountability. However, obstacles still faced are the accumulation of physical archives, limited storage space, and human error in archival management. To overcome these obstacles, the Bandung City Land Office implemented the PDCA (Plan, Do, Check, Action) approach as an effort to continuously improve the quality of archive management. This study concludes that digital-based archival management can optimally improve the effectiveness of public services.